Graying and staying on the job: The welfare implications of employment protection for older workers - Todd Morries; Benoît Dostie (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2023)
We study the welfare implications of employment protection for older workers, exploiting recent bans on mandatory retirement across Canadian provinces. Using linked employeremployee tax data, we show that the bans cause large and similar reductions in job separation rates and retirement hazards at age 65, with further reductions at higher ages. The effects vary substantially across industries and firms, and around two-fifths of the adjustments occur between ban announcement and implementation dates. We find no evidence that the demand for older workers falls, but the welfare effects are mediated by spillovers on savings behavior, workplace injuries, and spousal retirement timing.
Keywords: J26; J78; H55; 330; employment protection; retirement; welfare; active and passive savings responses; health effects; spousal spillovers